Proses Penyelesaian Perkara Perceraian Melalui Mediasi di Mahkamah Syar’iyah Lhokseumawe - Jumadiah Jumadiah (Universitas Lampung, 2012)
Marriage is one of elementary institution (basic institution) in law of Islam family, marriage is agreement which born from desire of a men and woman to coexist in tying akad. Marriage do not only have a meaning of the civil agreement, but also agreement owning meaning spiritual, later on will generate the rights and obligations of among/between spouse well-balancedly, however everybody do not can form an family which is is dreamed of the. Marriage can break and end because several things, that is because the happening of divorce which is is knocked down by husband to its wife, or because divorce that happened among/between both. Delivering birth nya of PERMA number 1 Year 2008 about Mediasi can assist the process of is solving of dispute of among/between spouse to obtain;get the agreement of the parties assistively by mediator. Mediasi one of process is solving of cheap and quicker dispute, and also can give to access the larger ones to the parties find the satisfying solution and fulfill sense of justice.